AB0049B CHANGES OF INNATE LYMPHOID CELLS IN PERIPHERAL BLOOD OF PATIENTS WITH PRIMARY SJöGREN'S SYNDROME AND ITS CORRELATIONS WITH CLINICAL MARKERS. (June 2019) - Chu, Hui; Tan, Zhen; Fang, Xuan; Wu, Ruolan; Wang, Ke; Xiangpei, LI; Wang, Guosheng; Wang, Yiping; Li, Xiaomei
Abstract : Background: Innate Lymphoid Cells (ILCs) are a novel group of innate immune cells, according to the cytokine profile, they were divided into three major subsets: ILC1(Lin–IL7R+NKp46+ILCs), ILC2(Lin–IL7R+CRTH2+ILCs) and ILC3(Lin–IL7R+CRTH2–CD117+ILCs) [1] . Little research on ILC in the pathogenesis of Primary Sjögren's Syndrome(primary SS) Objectives: Our purpose is to explore the function and role of ILC in the pathogenesis of Primary Sjögren's Syndrome and its correlations with clinical markers. Methods: 20 patients with pSS and 15 age-matched healthy non-immune-related diseases controls were enrolled. The frequency of ILCs, B cells, CD4+T and CD8+T cells from PBMCs was detected by flow cytometry. Analysis the subsets of ILCs in each group which compared with B cells and T cell subsets respectively and correlation with clinical serologic markers. Analyze the levels of IL-4, IL-9, IL-33, IL-22 and IFN-γ in each group by ELISA. Results: Compared with the control group, the percentage of ILC was decreased significantly in primary SS( P <0.0001); Meanwhile ILC1 was significantly increased in primary SS( P <0.0001), ILC2 was decreased significantly in primary SS( P =0.0009) and ILC3 has no significant difference in the primary SS ( P >0.05). The frequency of ILCs in all patients positively correlated with antinuclear antibody titer (ANA(D)) (r=0.295, P =0.0133), moreover, the frequency of ILC2 in primary SS was positively correlated with B cells(r=0.3896; p <0.05), and the serum IgG was negatively correlated with ILC2 of all patients (r=0.2091, P =0.0427). Compared with Healthy control group, the level of IL-22 was significant higher in primary SS( P =0.0003), however, the levels of IL-4, IL-9, IL-33 and IFN-γ were not significant different with healthy control group( P >0.05). Conclusion: The frequency of ILCs is related to ANA(D) of primary SS patients and ILCs play a critical role in the pathogenesis of primary SS. Its function and mechanism are worth further exploration. Reference: [1] Spits H., Artis D., Colonna M., et al. Innate lymphoid cells-a proposal for uniform nomenclature[J]. Nat Rev Immunol, 2013, 13(2): 145-149. doi: 10.1038/nri3365 Disclosure of Interests: None declared